Crataegus monogyna fruit aqueous extract as a protective agent against doxorubicin-induced reproductive toxicity in male rats - Ali Shalizar Jalali; Shapour Hasanzadeh (Mashhad University of Medical Sciences, 2013)
Objective: Doxorubicin (DOX) is a broad spectrum chemotherapeutic agent used in the treatment of several malignancies. The use of DOX in clinical chemotherapy has been restricted due to its diverse toxicities, including reproductive toxicity. Crataegus monogyna (C. monogyna) is one of the oldest medicinal plants that have been shown to be cytoprotective because of scavenging free radicals. The present study was undertaken to determine whether C. monogyna fruits aqueous extract could serve as a protective agent against reproductive toxicity during DOX treatment in a rat model through antioxidant-mediated mechanisms. Materials and Methods: Male Wistar rats were allocated to four groups. Two groups of rats were treated with DOX at a dose of 4 mg/kg intraperitoneally on days 1, 7, 14, 21, and 28 (accumulated dose of 20 mg/kg). One of the groups received C. monogyna fruits aqueous extract at a dose of 20 mg/kg per day orally for 28 days along with DOX. A vehicle-treated control group and a C. monogyna control group were also included. Results: The DOX-treated group showed significant decreases in the body and organ weights and spermatogenic activities as well as many histological alterations. DOX treatment also caused a significant decrease in sperm count and motility with an increase in dead and abnormal sperms. Moreover, significant decrease in serum levels of testosterone and increased serum concentrations of FSH, LH, LDH, CPK, and SGOT were observed in DOX-treated rats. Notably, Crataegus co-administration caused a partial recovery in above-mentioned parameters. Conclusion: These findings indicated that doxorubicin can adversely damage the testicular tissue, while Crataegus co-administrationcould effectively prevent these adverse effects by effective inhibiting oxidative processes and restoration of antioxidant defense system.